Financing vaccines in the 21st century : assuring access and availability (Online access: National Academy of Sciences National Academies Press., 2004)
The national immunization system has achieved high levels of immunization, particularly for children. However, this system faces difficult challenges for the future. Significant disparities remain in assuring access to recommended vaccines across geographic and demographic populations. These disparities result, in part, from fragmented public-private financing in which a large number of children and adults face limited access to immunization services. Access for adults lags well behind that of children, and rates of immunizations for those who are especially vulnerable because of chronic health conditions such as diabetes or heart and lung disease, remain low. "Financing Vaccines in the 21st Century: Assuring Access and Availability addresses these challenges by proposing new strategies for assuring access to vaccines and sustaining the supply of current and future vaccines. The book recommends changes to the Advisory Committee on Immunization Practices (AC1P)--the entity that currently recommends vaccines--and calls for a series of public meetings, a post-implementation evaluation study, and development of a research agenda to facilitate implementation of the plan.